Correlation Analysis between Chronic Osteomyelitis and Bacterial Biofilm - Kai Huang; Bingyuan Lin; Yiyang Liu; Haiyong Ren; Qiaofeng Guo (Stem Cells International)
Objective. To study the role of bacterial biofilm (BBF) in the formation of chronic osteomyelitis and its prevention and treatment. Methods. In this paper, a large amount of relevant literature was searched for analysis and summary, and the key words “chronic osteomyelitis,” “bacterial biofilm,” “infection,” and “debridement” were searched in databases, mainly CNKI, Wanfang, and Wipu. The search was conducted until December 2020. The role of bacterial biofilm formation in chronic osteomyelitis and its prevention were analyzed. Results. Chronic osteomyelitis is formed mainly due to poor blood supply and drug-resistant bacteria, of which cellular biofilm is the most important cause. BBF forms on the surface of necrotic soft tissue and bone tissue, which has a protective effect on bacteria and greatly enhances their resistance to antibiotics, leading to difficulties in complete bacterial clearance and recurrent infections in osteomyelitis. Conclusion. Through an in-depth study of the molecular biology and signal transduction of osteomyelitis biofilm, antibiotic biofilm treatment strategies and surgical debridement remain the focus of clinical translation of chronic osteomyelitis.